2015
DOI: 10.1515/sjecr-2015-0027
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Homocysteine Concentrations In Patients With Rheumatoid Arthritis

Abstract: In this study, we investigated the concentration of serum homocysteine (Hcy) in patients with rheumatoid arthritis (RA) compared with the control group and the connection between homocysteine and parameters of inflammation and disease activity. Sixty RA patients and 20 healthy controls were included in the study, and clinical examination and investigation were performed during which disease activity was assessed. Peripheral blood samples were used for all of the assays. Levels of Hcy were 33% higher in the RA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…The correlation between disease-related clinical characteristics among RA patients is demonstrated in Table 7. Hcys levels was strongly and significantly correlated with DAS28-CRP, CRP and ACCP Table (7 Similarly, same findings were detected by other studies (Vasiljevic et al,.2015, andAbd El-Aziz TA andMohamed RH. 2017).…”
Section: Correlation Between Disease-related Characteristics Among Ra...supporting
confidence: 78%
“…The correlation between disease-related clinical characteristics among RA patients is demonstrated in Table 7. Hcys levels was strongly and significantly correlated with DAS28-CRP, CRP and ACCP Table (7 Similarly, same findings were detected by other studies (Vasiljevic et al,.2015, andAbd El-Aziz TA andMohamed RH. 2017).…”
Section: Correlation Between Disease-related Characteristics Among Ra...supporting
confidence: 78%
“…Few studies, with equivocal results, examined homocysteine levels in rheumatoid arthritis patients [ 7 , 22 24 ]. Data have shown substantial elevation in homocysteine with rheumatoid arthritis due to abnormal homocysteine metabolism [ 7 , 22 , 24 ]. One study have found that homocysteine was 33% greater than healthy counterparts [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data have shown substantial elevation in homocysteine with rheumatoid arthritis due to abnormal homocysteine metabolism [ 7 , 22 , 24 ]. One study have found that homocysteine was 33% greater than healthy counterparts [ 22 ]. These abnormalities were attributed to low vitamin B 6 levels [ 7 ] and alteration in either the transsulfuration pathway or the regulation of the homocysteine cycle [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased serum HCY levels in patients with RA, in comparison to the general population, have been re ported by many authors [42][43][44].…”
Section: Homocysteine In Rheumatoid Arthritismentioning
confidence: 99%